DEKONSTRUKSI DALAM DESAIN URBAN STUDI KASUS: PLAZA E’X, JALAN M.H. THAMRIN, JAKARTA PUSAT - Fanty Puspita Dewi (LPPM, 2010)
An urban design is always interesting to be viewed. It is because an urban design belongs to the “urban” itself. So, an urban design must have a design that be able to facilitate the needs of the “urban”. The fast movement of Jakarta city needs an urban design which representing the fast movement of this city. A deconstruction concept can provide it. One example of urban design in Jakarta which using this concept in purpose is the E’X Plaza in Jalan Thamrin, Central Jakarta. The question research of this thesis is how the impact of the Plaza E’X as a deconstruction building to the Koridor Thamrin area in an urban context in the research area. What the writer wants to know is how the impact of architectural physical as a single building to a city, considered from the visual form of the image of the city in the area. The approach of this thesis is using the descriptive qualitative method and phenomenological method. This phenomenological method lets the area to tell the story of itself to the writer as a viewer, about the phenomena in it, and then it described qualitatively by the writer from the single first person’s point of view, in this case is the writer as a direct observer. The theory those used to help the writer tells the story about the E’X Plaza as a single building and the connection with the urban area is the deconstruction theory as the architectural approach, and the urban theories, one as the approach by Kevin Lynch with its five elements which formed the image of the city. Finally, there is a conclusion that functionally the E’X Plaza give the answer of the user’s needs of the entertainment center in that area which have its own style and class, for the young, funky and exclusive executive. Its existency works together with other buildings with different function, such as offices, embassy and hotels. But if it put inside a city visual form, the deconstruction concept of this building doesn’t give a strong impact to the visual form of the whole Thamrin area. Keywords : urban, kevin lynch, the image of the city, deconstruction, thamrin area